Institutional Management and Quality Assurance in Quranic Education Effectiveness - Zainul Fuad; Imam Azhar; Zulkarnain Zulkarnain; Imam Karya Bakti (JUMPA : Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the effectiveness of Ummi Method implementation in Quranic education and to identify the institutional factors influencing its success across educational institutions in Indonesia. A quantitative approach with a descriptive-comparative design and limited longitudinal elements was employed, involving 127 institutions selected through purposive and stratified sampling techniques. Data were collected using the standardized Ummi Method Learning Supervision Form, which encompasses eight evaluation dimensions, and analyzed using descriptive statistics, ANOVA, paired t-tests, and correlation analysis. The findings indicate that the overall effectiveness of implementation is at a fair-to-good level (M = 3.54), with significant variation across institutions. Learning preparation achieved the highest performance, while evaluation and closing dimensions showed comparatively weaker results. Longitudinal analysis reveals significant improvement over time (p < 0.001), suggesting ongoing institutional development. Notably, management effectiveness demonstrates the strongest positive correlation with learning outcomes (r = 0.67), followed by teacher certification and community engagement, whereas institutional size shows a weak negative correlation. These findings highlight that the effectiveness of Quranic education is not solely determined by instructional methods but is fundamentally influenced by institutional management systems, teacher competency, and quality assurance mechanisms. The study underscores the importance of strengthening institutional capacity, enhancing teacher professionalism, and implementing systematic evaluation frameworks to ensure sustainable improvement in Quranic education.